PENTERJEMAHAN DIMENSI SOSIAL KATA TABU DALAM NOVEL THE CATCHER IN THE RYE: THE TRANSLATION OF TABOO WORDS SOCIAL DIMENSION IN THE CATCHER IN THE RYE NOVEL - Fadzil, Nur Anis; Abdul Sukur, Anis Shahirah (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract This article is a qualitative study examining social dimensions as a factor influencing the translation of taboo words. The social dimension is a component in sociolinguistics that unravels social information of the community within the communication process. Data were retrieved from a novel titled ‘The Catcher in the Rye’ by J.D. Salinger in 1951. The translated version in the Malay language was titled ‘Wira Ladang’, which Zulkifli Ahmad translated in 1999. In this novel, J.D. Salinger narrated the story of a teenage rebellion icon named Holden Caulfield. The social dimension framework by Holmes & Wilson (2017) and translation strategy by Baker (2011) were applied in this study. The study showed that four social dimensions by Holmes & Wilson (2017) – social distance, social status, formality and function – are significant factors in determining strategies used by the translator to address taboo words in translation. The researchers also found that textual formality is a dominant social dimension factor influencing the translation of taboo words. However, other social dimensions did influence the selection of strategies by the translator in translating taboo words. This study can serve as a guide for literary work translators to determine the strategy in translating social dimensions that best suit the norms and culture of Malaysian readers. Keywords: social dimension, taboo word, sociolinguistics, translation strategy, culture.